STUDI KONSEP PENDIDIK DAN PESERTA DIDIK : PEMIKIRAN ABUDDIN NATA DAN ZAKIAH DARADJAT - Farichah, Eneng (Jurnal Ilmiah Pendidikan dan Keislaman, 2024)
This study aims to determine the concept of educators and students and the purpose of this study is to determine how the concept of educators and students think of Abuddin Nata and Zakiah Daradjat. This study is a library research (library research). The primary data sources are the book "Islamic Education Science and Islamic Perspectives on Learning Strategies" by Abuddin Nata, the book "Islamic Education Science and Special Methods for Teaching Islamic Religion" by Zakiah Daradjat. While the secondary data are books that are relevant to this study. The data collection technique uses documentation and the analysis used is content analysis (calculation analysis). The results of this study provide the conclusion that first, the concept of educators according to Abuddin Nata is someone who is knowledgeable and broad-minded, has skills, experience, has a noble personality, understands the explicit and implicit, becomes an example and model for students. Second, the concept of educators according to Zakiah Daradjat is a professional educator who is able to foster all the abilities and good attitudes of students, as a teacher who guides and fosters the development of knowledge, attitudes and skills. Third, Abuddin Nata's concept of a learner involves not only children but also adults. While the term "student" refers exclusively to children, learners are also partners in teaching and learning activities. Fourth, Zakiah Daradjat's concept of a learner is that they are unique individuals with potential and are undergoing a development process. Learners are both subjects and objects in teaching and learning interactions, receiving lessons and guidance from educators